Preoperative vs Postoperative Patient Outcome and Recovery Expectations of Total Joint Arthroplasty - Siddhartha Dandamudi, BBA; Kyleen Jan, MD; Madelyn Malvitz, BS; Anne DeBenedetti, MSc; Omar Behery, MD, MPH; Brett R. Levine, MD, MS (Arthroplasty Today, 2025)
Background: Patient satisfaction with total joint arthroplasty (TJA) remains a challenge, with up to 20% of patients expressing dissatisfaction despite good clinical outcomes. This study aims to assess patient expectations and experiences prior to and after undergoing a primary TJA. Methods: A 13-question survey assessing patient expectations around surgical risks, logistics, physical therapy (PT), and pain was distributed in the clinics of multiple surgeons at an academic center. Each patient was categorized as either preoperative or postoperative, with similar questions for both groups. No identifying information was collected. Results: One hundred eight preoperative and 344 postoperative responses were collected. Preoperatively, 91.3% of patients felt they had enough time to ask questions compared to 98.5% (P = .01) postoperatively. Preoperative patients named risks of TJA more accurately (P < .00001). Expectations of long-term pain differed: 48.3% of preoperative patients expected no pain and 1.7% expected to be unable to move; postoperatively, 7.3% (P < .0001) reported no pain and 10.3% (P = .03) were unable to move; 17.3% of patients finished PT within 2 weeks, compared to 1.7% who believed this was possible (P =.0027). A total of 73.1% of postoperative patients requested additional weeks of PT. Only 52.1% or patients had a long-term follow-up plan in place. Conclusions: Expectations vary in patients undergoing TJA. Preoperative patients may have unrealistic expectations regarding postoperative pain and mobility. The need for more PT and the lack of a long-term follow-up plan highlight the importance of comprehensive perioperative communication to align expectations and potentially improve satisfaction and follow-up compliance.